Jazz dance : a history of the roots and branches - Guarino, Lindsay; Oliver, Wendy (University Press of Florida, 2014)
This collection of essays tells the story of jazz dance past and present, focusing on history, not technique. This anthology examines trends, influences, training, race and gender issues, aesthetics and the international appeal of jazz dance.